COVID-19 in Latin America: A Bibliometric Analysis of Scientific Publications in Health - Gallegos de San Vicente, Miguel Omar (2020)
The coronavirus disease (COVID-19) has become a global health crisis. The scientific community has responded with a sizable level of research and publications, many of which are beginning to be identified and analyzed in systematic reviews of the literature and bibliometric studies. No readily identifiable, comparable study focused on Latin American scientific literature has been undertaken thus far. Therefore, this article analyzes such literature, focused on COVID-19, and one that has been published in the scientific journals of the region. A search with the keyword “COVID-19” in the Scientific Electronic Library Online (SciELO) database resulted in the identification of 261 documents. Following PRISMA guidelines, the total number was reduced to 117 for the purpose of the bibliometric analysis (i.e., elimination of preprint duplicates). Such analysis resulted in the following findings: 69 publications were editorial or individual commentaries, and 48 were original articles. The male authors totaled 280, contrasted with 169 female authors. Two Brazilian journals led in the number of publications: Cadernos de Saúde Pública and Clinics. Even though the Latin American scientific productivity regarding COVID-19 is not well represented in the different databases of the region, it is expected that these scientific publications will achieve increased visibility in the coming months. The article emphasizes the importance of systematic and bibliographic reviews ofthe scientific literature in Latin America in orderto evaluate the public health achievements of the region.